Involvement of desat1 gene in the control of Drosophila melanogaster pheromone biosynthesis. - Labeur, C.; Dallerac, R.; Wicker-Thomas, C. (Genetica, 2002)
Cuticular pheromones in Drosophila melanogaster are unsaturated hydrocarbons with at least one double bond in position 7: 7-tricosene and 7-pentacosene in males and 7,11 -heptacosadiene and 7,11 -nonacosadiene in females. We have previously shown that a desaturase gene, desat1, located in chromosome region 87 C could be involved in this process: the Desat1 enzyme preferentially leads to the synthesis of palmitoleic acid, a precursor of omega7 fatty acids and 7-unsaturated hydrocarbons. Therefore, we have searched for P-elements in the 87 region and mapped them. One was found inserted into the first intron of the desat1 gene. Flies heterozygous for this insertion showed a large decrease in the level of 7-unsaturated hydrocarbons, comparable to that observed in flies heterozygous for a deficiency overlapping desat1. Less than 1 % of flies homozygous for this insertion were viable. They were characterized by dramatic pheromone decreases. After excision of the transposon, the pheromone phenotype was reversed in 69% of the lines and the other excision lines had more or less decreased amounts of 7-unsaturated hydrocarbons. All these results implicate desat1 in the synthesis of Drosophila pheromones.